Sunset: a survey and analysis of the state experience - Kearney, Richard C.
Sunset legislation was adopted by 36 states from 1976 to 1982. This article reviews the published research om Sunset and reports on a 1988-89 survey of Sunset adopters. Results indicate that Sunset has resulted in some agency terminations and more importantly, numerous substantive, procedural and cross-cutting modifications aimed at increasing accountability, efficiency, and effectiveness in state agencies. However, 12 states have ceased the use of this legislative oversight mechanism because of high monetary and temporal costs of Sunset review, extensive lobbying by vested interests, unfulfilled expectations of aency termination, low levels of citizen participation, and other perceived problems
Keywords: Survey; Legislature; Legislative Control of Administration